Method for removing antimony by using zirconium functionalized adsorbent resin

By modifying and fixing the surface of the polymer substrate and zirconium oxychloride, functionalized adsorption resin is prepared, which solves the problems of low removal efficiency and poor material stability in the prior art, and realizes the mineral tunnel Efficient recycling and reuse of antimony in influx water.

CN119409264AActive Publication Date: 2025-02-11YANGLING HESHENG IRRADIATION TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411588602.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove low concentrations of antimony and its recovery in mine inrush water, and some adsorbent materials decompose under acidic conditions or lack mechanical strength.

Method used

By modifying the surface of the polymer substrate, unsaturated monomers of epoxy groups or halogen, and fixing zirconium oxychloride through chelation reaction, zirconium functionalized adsorption resin was prepared. The resin has high affinity for antimony ions within the pH range of 1-11, and is eluted and concentrated and separated by leaching solution.

Benefits of technology

It realizes efficient adsorption and recovery of low concentrations of antimony, which is especially suitable for antimony recovery in mine inrush water, and has good reusability and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005124940110000011
    Figure FDA0005124940110000011
  • Figure HDA0005124940150000011
    Figure HDA0005124940150000011
  • Figure HDA0005124940150000012
    Figure HDA0005124940150000012
Patent Text Reader

Abstract

The invention provides a method for removing antimony by using zirconium functionalized adsorption resin, and belongs to the field of environmental protection. Comprising the following steps: (1) adjusting the pH value of a solution containing antimony ions to 1-11, and then adding zirconium functionalized adsorption resin into the solution to adsorb the antimony ions in the solution containing the antimony ions; and 2) after adsorption is finished, eluting, concentrating, separating and regenerating antimony loaded on the zirconium functionalized adsorption resin by adopting an eluent, so as to realize removal of antimony. According to the method disclosed by the invention, key reaction participants of the method are improved, and the zirconium-functionalized adsorption resin material is applied to antimony recovery, particularly can be applied to adsorption of low-content antimony in mine cavern gushing water, and also can be used for removing arsenic with relatively strong toxicity. The method is easy to operate and suitable for large-scale recovery of low-concentration antimony.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection, and specifically relates to a method for removing antimony by utilizing zirconium functionalized adsorption resin. Based on this method, low-concentration antimony can be recovered from actual mine water. Background Art

[0002] Antimony is the fifth major non-renewable strategic metal. Antimony and its compounds are widely used in ceramics, pigments, plastics, batteries, pyrotechnics, alloys and flame retardants. Generally speaking, the toxicity of various antimonies is in the following order: Sb(III)>Sb(V)>organic antimony compounds. However, antimony has high cumulative toxicity and carcinogenicity to the human body. Therefore, in order to protect human health, many countries and organizations have listed antimony as a priority pollutant.

[0003] According to the research of existing literature, the treatment of antimony is mainly divided into membrane separation technology, ion exchange, coagulation / flocculation, electrochemical technology, adsorption, etc. Generally speaking, membrane separation technology and ion exchange technology can achieve a high removal efficiency, but the investment and operating costs hinder their development; coagulation technology and electrochemical technology are more practical, but there is also a risk of secondary pollution. Among them, the adsorption method is currently the best method for treating antimony due to its simple operation, safety, low cost and high efficiency. In addition, adsorption technology is suitable for the treatment of low-concentration metal ions. The most critical part of the adsorption method is the adsorbent. In order to cope with the high demand for antimony in industrial life and production and reduce the environmental pollution caused by antimony, it is very important to design efficient zirconium-functionalized adsorption resins to remove antimony.

[0004] The introduction of high-valent metal elements such as zirconium, iron and titanium can show good affinity for antimony. Many literatures have adopted similar ideas to achieve higher antimony adsorption than before modification. It is reported that some titanium-functionalized composite adsorbent materials will decompose under acidic conditions. At the same time, some ferrite-functionalized composite materials have low adsorption capacity and lack mechanical strength, which hinders the practical application of these materials. Zirconium, as an inorganic material, has the characteristics of non-toxicity, chemical inertness and insolubility in water, and has a higher affinity for antimony ions. This provides a theoretical basis for the use of zirconium-functionalized compound adsorbents to treat highly toxic antimony in water. Therefore, the development of zirconium-functionalized adsorption resins for efficient removal of antimony is of great significance to environmental protection and human health. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a method for removing antimony using a zirconium-functionalized adsorption resin. The purpose of the present invention is to use a zirconium-functionalized compound adsorbent to treat highly toxic antimony ions in water, and to modify the surface of the substrate to maximize the zirconium functionalization of the adsorption resin surface, making it suitable for large-scale recovery of low-concentration antimony.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for removing antimony using zirconium functionalized adsorption resin comprises the following steps:

[0008] Step 1): adjusting the pH of the solution containing antimony ions to 1-11, and then adding zirconium functionalized adsorption resin thereto to adsorb the antimony ions in the antimony ion-containing solution;

[0009] Step 2): After the adsorption is completed, the antimony loaded on the zirconium functionalized adsorption resin is eluted, concentrated, separated and regenerated using an eluent to achieve the removal of the antimony.

[0010] Wherein, in the above step 1), the zirconium-functionalized adsorption resin is a zirconium-functionalized adsorption resin obtained by surface modification of a polymer substrate; the chemical structure of the zirconium-functionalized adsorption resin is: in, represents polymer substrate;

[0011] Specifically, the surface modification method of the zirconium functionalized adsorption resin comprises the following steps:

[0012] Step (a): firstly grafting an unsaturated monomer containing an epoxy group or a halogen onto the surface of a polymer substrate to modify the substrate to form a functional intermediate I;

[0013] The mass ratio of the polymer substrate to the unsaturated monomer emulsion containing epoxy groups or halogens is (1-2):(5-20), and the unsaturated monomer emulsion containing epoxy groups or halogens contains 30% by mass of the unsaturated monomer containing epoxy groups or halogens;

[0014] Step (b): further introducing a compound having sodium carboxylate on the surface of the functional intermediate I through an epoxy ring-opening reaction or a halogenation reaction to obtain a functional intermediate II;

[0015] Wherein, the mass ratio of the functional intermediate I to the compound having sodium carboxylate is (1-2): (10-20);

[0016] Step (c): finally, a chelating reaction is carried out between the carboxyl group of the functional intermediate II and zirconium oxychloride ZrOCl2, thereby obtaining a zirconium functionalized adsorption resin for recovering antimony;

[0017] Wherein, the mass ratio of the functional intermediate II to zirconium oxychloride is (1-2): (10-20).

[0018] As a further preferred embodiment of the present invention, in the above step (a), the polymer substrate is selected from one of cellulose, lignin, chitosan or its derivatives, polyethylene, polypropylene, polystyrene, polystyrene-divinylbenzene copolymer, ethylene-vinyl alcohol copolymer, and polyamide;

[0019] The crystallinity of the cellulose or its derivative is above 80%.

[0020] As a further preference of the present invention, in the above step (a), the unsaturated monomer containing epoxy group or halogen is selected from one of glycidyl methacrylate GMA, allyl alcohol glycidyl ether, glycidyl acrylate, chloroethyl methacrylate, chloroethyl acrylate, and chloromethylstyrene.

[0021] As a further preferred embodiment of the present invention, in the above step (b), the compound having sodium carboxylate is one of sodium iminodiacetic acid, sodium aminoacetate and sodium alanine.

[0022] As a further preferred embodiment of the present invention, in the above step (a), the grafting method for modifying the surface of the polymer substrate specifically adopts an ionizing radiation grafting method or a chemical grafting method;

[0023] The ionizing radiation grafting method is electron beam pre-radiation grafting, and the irradiation dose used in the electron beam pre-radiation grafting is preferably 10 to 100 kGy;

[0024] The chemical grafting method is grafted by using an initiator; the initiator is preferably an organic peroxide or an azo initiator, wherein the organic peroxide is preferably cyclohexanone peroxide, dibenzoyl peroxide or tert-butyl hydroperoxide; the azo initiator is preferably azobisisobutyronitrile or azobisisoheptanenitrile.

[0025] As a further preference of the present invention, in the above step (b), when the compound containing sodium carboxylate is further introduced onto the surface of the polymer substrate through the epoxy ring-opening reaction, it is specifically achieved through a solvothermal reaction; the solvent used in the solvothermal reaction is water, methanol, toluene, ethylene glycol or N,N-dimethylformamide, and the reaction temperature of the solvothermal reaction is 80-140°C.

[0026] As a further preference of the present invention, in the above step (c), when zirconium functionalization is achieved by reacting sodium carboxylate and zirconium oxychloride, it is specifically achieved by a hydrothermal reaction; the concentration of the zirconium oxychloride solution used in the hydrothermal reaction is 10-20wt%, and the reaction temperature of the hydrothermal reaction is 80-120°C.

[0027] As a further preferred embodiment of the present invention, the polymer substrate is spherical, fibrous or film-shaped; accordingly, the obtained zirconium functionalized adsorption resin is also spherical, fibrous or film-shaped;

[0028] Preferably, the average particle size of the spherical resin that can be used for filling the adsorption column is between 100 and 1000 μm.

[0029] As a further preferred embodiment of the present invention, in the above step 1), the antimony-containing solution mainly comprises a leaching solution of stibnite, stibnite, antimony ochre, or antimony-containing groundwater;

[0030] As a further preferred embodiment of the present invention, in the above step 2), the eluent is 1 mol / L to 3 mol / L sodium hydroxide solution.

[0031] The advantages of the present invention compared with the prior art are:

[0032] 1. In order to maximize the functionalization of zirconium on the surface of the adsorption resin, this scheme uses ionizing radiation grafting or chemical grafting to first introduce unsaturated monomers containing epoxy groups or halogens onto the substrate in the design of the adsorption material structure, and then modify the grafted substrate with carboxyls, and chelate and fix the zirconium compound on the surface of the adsorption resin through carboxyl groups to obtain a zirconium-functionalized adsorption resin, thereby providing a large number of active sites; the adsorption separation material obtained by this method is particularly suitable for the efficient adsorption of low-concentration antimony;

[0033] 2. The zirconium-functionalized adsorption resin synthesized in this scheme has its surface modified with abundant zirconium ions having high affinity with antimony ions; the zirconium oxychloride introduced on the substrate by the adsorption resin can, on the one hand, undergo anion exchange with antimony ions; on the other hand, it can coordinate with antimony ions through the lone electron pair on the zirconium-oxygen double bond, thereby achieving efficient adsorption of antimony;

[0034] 3. This scheme improves the key reaction participants in the method and applies zirconium-functionalized adsorption resin materials to the recovery of antimony. It can be especially used for the adsorption of low-content antimony in mine water and can also remove highly toxic arsenic at the same time. It is simple to operate and suitable for large-scale recovery of low-concentration antimony. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The synthetic route of the zirconium functionalized adsorption resin in the present invention is as follows;

[0036] Figure 2 The adsorption results of Sb(III) by zirconium functionalized adsorption resin at different pH in the embodiment of the present invention;

[0037] Figure 3 The adsorption results of Sb(V) by zirconium functionalized adsorption resin at different pH in the embodiment of the present invention;

[0038] Figure 4The adsorption results of zirconium functionalized adsorption resin on different concentrations of Sb(III) in the embodiment of the present invention;

[0039] Figure 5 The adsorption results of zirconium functionalized adsorption resin on different concentrations of Sb(V) in the embodiment of the present invention;

[0040] Figure 6 The experimental result diagram of the repeated utilization of antimony by zirconium functionalized adsorption resin in the embodiment of the present invention;

[0041] Figure 7 The static adsorption experimental results of antimony in mine water by zirconium functionalized adsorption resin in the embodiment of the present invention are shown in FIG.

[0042] Figure 8 The results of the dynamic adsorption experiment of antimony in the mine water by the zirconium functionalized adsorption resin in the embodiment of the present invention are shown in FIG.

[0043] Fig. 9 The results of the dynamic elution experiment of antimony from mine water by zirconium functionalized adsorption resin in the embodiment of the present invention are shown in FIG. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the following Figure 1-9 The present invention is further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other. In addition, after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0045] Based on the method of the present invention, the specific operation can be divided into an adsorption process and an elution process. Specifically, a zirconium-functionalized adsorption resin is added to the solution to adsorb antimony, or the antimony-containing solution is flowed into an adsorption column filled with a zirconium-functionalized adsorption resin material through a peristaltic pump; after the adsorption is completed, the antimony loaded on the material is eluted and separated using a corresponding eluent.

[0046] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0047] Example 1: Synthesis of zirconium-functionalized adsorption resin

[0048] The synthetic route of zirconium functionalized adsorption resin is as follows Figure 1As shown. 5.00g of microcrystalline cellulose microspheres (Celp) were vacuum sealed and passed through a 1MeV electron beam accelerator under dry ice cooling (irradiation dose rate of 10kGy / pass, irradiation dose of 10kGy). Then, the irradiated Celp was placed in 50g of GMA emulsion (30% GMA, 3% surfactant Tween 20) and reacted in a 50°C water bath for 2h. The product was washed with ethanol and vacuum dried at 60°C to obtain Celp-g-GMA. 1g of Celp-g-GMA was placed in a 20wt% sodium iminodiacetic acid aqueous solution and reacted at 80°C for 12h. The reaction product was washed, filtered and dried to obtain Celp-g-GMA-IDA. Then, 1 g of Celp-g-GMA-IDA was put into a 10 wt % zirconium oxychloride aqueous solution and reacted at 80° C. for 12 h. The reaction product was washed, filtered, and dried to obtain the zirconium-functionalized adsorption resin Celp-g-GMA-IDA-ZrOCl2.

[0049] In Examples 2 to 9, Celp-g-GMA-IDA-ZrOCl2 zirconium functionalized adsorption resin was used to explore the removal effect of this type of adsorption material on antimony.

[0050] Example 2: Adsorption of Sb(III) by zirconium functionalized adsorption resin at different pH values

[0051] Weigh 0.01g of adsorption resin and put it into 10mL of aqueous solution containing antimony at 30℃ for static batch adsorption experiment. Use 0.1mol / L HCl and NaOH to adjust the pH of the solution to 1-11 respectively, and conduct adsorption experiment. After adsorption for a period of time, filter out the supernatant with a filter head, detect the concentration of metal ions with ICP-OES, and calculate its adsorption efficiency.

[0052] The adsorption results of Sb(III) on zirconium functionalized adsorption resin at different pH are shown in Figure 2. Figure 2 As shown in the figure, it can be seen that the adsorption of Sb(III) by zirconium functionalized adsorption resin is almost unaffected by pH, indicating that the material can be used in a wide pH range.

[0053] Example 3: Adsorption of Sb(V) by zirconium functionalized adsorption resin at different pH values

[0054] The zirconium functionalized adsorption resin was used for the adsorption of Sb(V) using similar adsorption steps as in Example 2. After a period of adsorption, the supernatant was filtered out with a filter head, and the residual antimony concentration was detected by ICP-OES, and the adsorption efficiency was calculated.

[0055] The adsorption results of Sb(V) on zirconium functionalized adsorption resin at different pH are shown in Figure 2. Figure 3As shown in the figure, it can be seen that the adsorption efficiency of zirconium functionalized adsorption resin at different pH is similar to the adsorption result of Sb(III), indicating that the material can be used in a wide pH range.

[0056] Example 4: Adsorption of Sb(III) at different concentrations by zirconium functionalized adsorption resin

[0057] Weigh 0.01 g of adsorption resin and put it into 10 mL of Sb(III) solution with different concentrations at 30°C to conduct a static batch adsorption experiment. After a period of adsorption, filter out the supernatant with a filter head, detect the ion concentration with ICP-OES, and calculate its adsorption efficiency.

[0058] The adsorption results of zirconium functionalized adsorption resin for different concentrations of Sb(III) are shown in Figure 2. Figure 4 As shown in the figure, it can be seen that with the increase of Sb(III) concentration, the adsorption amount of Sb(III) by zirconium functionalized adsorption resin gradually increases. The isotherm adsorption data was fitted with Langmuir and Freundlich models, and it was found that the adsorption process of Sb(III) conforms to the Langmuir model, and the maximum adsorption amount is 56.25 mg / g.

[0059] Example 5: Adsorption of Sb(V) at different concentrations by zirconium functionalized adsorption resin

[0060] The zirconium functionalized adsorption resin was used for the adsorption of Sb(V) at different concentrations using similar adsorption steps as in Example 4. After a period of adsorption, the supernatant was filtered out with a filter head, and the residual antimony concentration was detected by ICP-OES, and its adsorption efficiency was calculated.

[0061] The adsorption results of zirconium functionalized adsorption resin for different concentrations of Sb(V) are shown in Figure 2. Figure 5 As shown in the figure, it can be seen that with the increase of Sb(V) concentration, the adsorption amount of Sb(V) by zirconium functionalized adsorption resin gradually increases. The isotherm adsorption data was fitted with Langmuir and Freundlich models, and it was found that the adsorption process of Sb(V) conforms to the Langmuir model, and the maximum adsorption amount is 240.96 mg / g.

[0062] Example 6: Experiment on the reuse of antimony by zirconium functionalized adsorption resin

[0063] Weigh 0.01g of adsorption resin and put it into 10mL of aqueous solution containing antimony at 30℃. After adsorption for a period of time at natural pH, filter out the supernatant with a filter head, detect the residual antimony concentration with ICP-OES and calculate its removal rate. Wash the antimony-loaded resin three times with deionized water, and add 1mol / L NaOH solution as eluent for elution. Wash the resin with deionized water three times for each adsorption experiment, and then carry out the next cycle. Repeat this cycle five times.

[0064] The experimental results of the repeated use of antimony by zirconium functionalized adsorption resin are as follows: Figure 6 As shown in the figure, it can be concluded that after five cycles, the adsorption efficiency of zirconium functionalized adsorption resin for antimony remains basically unchanged, indicating that this adsorption material has good reusability in the process of removing antimony.

[0065] Example 7: Static adsorption experiment of antimony in mine water by zirconium functionalized adsorption resin

[0066] Weigh 0.01g of adsorption resin and put it into 10mL of antimony-containing mine water at 30℃ to conduct a static batch adsorption experiment. After a period of adsorption, filter out the supernatant with a filter head, detect the ion concentration with ICP-OES, and calculate its adsorption efficiency.

[0067] The adsorption results of zirconium functionalized adsorption resin on antimony in mine water are as follows: Figure 7 As shown in the figure, it can be concluded that the zirconium-functionalized adsorption resin can not only efficiently adsorb antimony from groundwater, but also adsorb the toxic ion arsenic at the same time.

[0068] Example 8: Dynamic adsorption experiment of antimony in mine water by zirconium functionalized adsorption resin

[0069] The zirconium functionalized adsorption resin is filled into the adsorption column in a wet state, and the antimony-containing groundwater is pumped into the adsorption column. Dynamic adsorption evaluation conditions: The adsorption column volume is 1mL, and a certain amount of zirconium functionalized adsorption resin is filled. The antimony concentration of the mine water containing antimony is 10.16mg / L.

[0070] According to the above experimental conditions, a dynamic adsorption experiment was conducted and the results were obtained by sampling and analyzing at specific time intervals. Figure 8 The results show that zirconium-functionalized adsorption resin can effectively remove antimony from mine water, indicating that this zirconium-functionalized resin has the potential to remove antimony on an industrial scale.

[0071] Example 9: Dynamic elution experiment of antimony in mine water by zirconium functionalized adsorption resin

[0072] 1 mol / L sodium hydroxide was used as the eluent to elute the zirconium functionalized adsorption resin loaded with antimony in Example 8. Fig. 9It can be seen from the desorption experimental results that only 20BV of eluent is needed to achieve an elution rate of more than 99%.

[0073] It can be seen from the above examples that the method improves the key reaction participants and applies the zirconium-functionalized adsorption resin material to the recovery of antimony. It can be especially used for the adsorption of low-content antimony in mine water and can also remove the highly toxic arsenic at the same time. The operation is simple and suitable for large-scale recovery of low-concentration antimony.

[0074] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0075] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for removing antimony using zirconium functionalized adsorption resin, characterized in that: The following steps are involved: Step 1): adjusting the pH of the solution containing antimony ions to 1-11, and then adding zirconium functionalized adsorption resin thereto to adsorb the antimony ions in the antimony ion-containing solution; Step 2): After the adsorption is completed, the antimony loaded on the zirconium functionalized adsorption resin is eluted, concentrated, separated and regenerated using an eluent to achieve the removal of the antimony.

2. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 1, characterized in that: In the above step 1), the zirconium-functionalized adsorption resin is a zirconium-functionalized adsorption resin obtained by surface modification of a polymer substrate; the chemical structure of the zirconium-functionalized adsorption resin is: in, represents polymer substrate; The surface modification method of the zirconium functionalized adsorption resin comprises the following steps: Step (a): firstly grafting an unsaturated monomer containing an epoxy group or a halogen onto the surface of a polymer substrate to modify the substrate to form a functional intermediate I; The mass ratio of the polymer substrate to the unsaturated monomer emulsion containing epoxy groups or halogens is (1-2):(5-20), and the unsaturated monomer emulsion containing epoxy groups or halogens contains 30% by mass of the unsaturated monomer containing epoxy groups or halogens; Step (b): introducing a compound having sodium carboxylate on the surface of the functional intermediate I through an epoxy ring-opening reaction or a halogenation reaction to obtain a functional intermediate II; Wherein, the mass ratio of the functional intermediate I to the compound having sodium carboxylate is (1-2): (10-20); Step (c): finally, a chelating reaction is carried out between the carboxyl group of the functional intermediate II and zirconium oxychloride ZrOCl2 to obtain a zirconium functionalized adsorption resin; Wherein, the mass ratio of the functional intermediate II to zirconium oxychloride is (1-2): (10-20).

3. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 2, characterized in that: In the above step (a), the polymer substrate is selected from one of cellulose, lignin, chitosan or its derivatives, polyethylene, polypropylene, polystyrene, polystyrene-divinylbenzene copolymer, ethylene-vinyl alcohol copolymer, and polyamide; The crystallinity of the cellulose or its derivative is above 80%.

4. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 2, characterized in that: In the above step (a), the unsaturated monomer containing epoxy group or halogen is selected from one of glycidyl methacrylate GMA, allyl alcohol glycidyl ether, glycidyl acrylate, chloroethyl methacrylate, chloroethyl acrylate, and chloromethylstyrene.

5. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 2, characterized in that: In the above step (b), the compound having sodium carboxylate is one of sodium iminodiacetic acid, sodium aminoacetate and sodium alanine.

6. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 2, characterized in that: In the above step (a), the grafting method for modifying the surface of the polymer substrate is an ionizing radiation grafting method or a chemical grafting method; The ionizing radiation grafting method is electron beam pre-radiation grafting, and the irradiation dose used in the electron beam pre-radiation grafting is preferably 10 to 100 kGy; The chemical grafting method is grafted by using an initiator; the initiator is preferably an organic peroxide or an azo initiator, wherein the organic peroxide is preferably cyclohexanone peroxide, dibenzoyl peroxide or tert-butyl hydroperoxide; the azo initiator is preferably azobisisobutyronitrile or azobisisoheptanenitrile.

7. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 2, characterized in that: In the above step (b), when the compound containing sodium carboxylate is introduced onto the surface of the polymer substrate through the epoxy ring-opening reaction, it is specifically achieved through a solvent thermal reaction; the solvent used in the solvent thermal reaction is water, methanol, toluene, ethylene glycol or N,N-dimethylformamide, and the reaction temperature of the solvent thermal reaction is 80 to 140°C.

8. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 2, characterized in that: In the above step (c), when zirconium functionalization is achieved by reacting sodium carboxylate and zirconium oxychloride, it is specifically achieved by a hydrothermal reaction; the concentration of the zirconium oxychloride solution used in the hydrothermal reaction is 10-20wt%, and the reaction temperature of the hydrothermal reaction is 80-120°C.

9. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 2, characterized in that: The polymer substrate is spherical, fibrous or film-shaped; accordingly, the obtained zirconium functionalized adsorption resin is also spherical, fibrous or film-shaped; When the zirconium functionalized adsorption resin is a spherical resin, the average particle size of the spherical resin is 100-1000 μm.

10. The method for removing antimony by using zirconium functionalized adsorption resin according to claim 1, characterized in that: In the above step 1), the antimony-containing solution mainly includes the leaching solution of stibnite, stibnite, antimony ochre, or antimony-containing groundwater; In the above step 2), the eluent is 1 mol / L to 3 mol / L sodium hydroxide solution.

Citation Information

Patent Citations

  • Novel sorbent, method of producing the same and the use thereof

    CN102458649A

  • Bio-adsorbent prepared by modifying sodium carboxymethyl starch as well as preparation method and use method of bio-adsorbent

    CN105561931A

  • Adsorbent for adsorbing iodine compounds and / or antimony, method for preparing said adsorbent, and method and apparatus for treating radioactive waste liquid by using said adsorbent

    CN107847902A

  • Tubular titanium dioxide nano composite Sb adsorbent loaded with zirconium dioxide and ferroferric oxide and preparation method and application thereof

    CN109621883A

  • Method for adsorbing and stripping off antimony from antimony-containing wastewater

    CN110316793A